Severe and uncontrolled asthma in China: a cross-sectional survey from the Australasian Severe Asthma Network - Wang, Gang (J Thorac Dis, 2017)
BACKGROUND: Severe asthma is largely unexplored in the Chinese population. Patients with asthma underwent systematic evaluation, by investigating the characteristics of uncontrolled asthma and of asthma treated with three different controller therapies. METHODS: This multi-centre, real-world study was conducted from March 2014 to September 2015. Adults with stable asthma underwent assessment of medication use, asthma control, quality of life, psychological symptoms, work productivity and activity impairment, bronchodilator response and sputum induction. RESULTS: Participants (n=379) had a mean (SD) age of 47.4 (14.0) years, and 57.0% were female. There were 14.8% (n=56) of patients receiving treatment with Step 4/5 as severe asthma, but only 13 (3.4%) met ERS/ATS severe refractory asthma criteria. The patients with severe asthma usually used triple controller therapy: ICS/LABA, additional leukotriene modifier or theophylline, and reported better asthma control. Two fifths of patients (n=147) had uncontrolled asthma, with worse symptoms, psychological symptoms (both P<0.001), health-related work productivity and activity impairment, increased eosinophilic inflammation in sputum [1.68% (0.0, 17.1%) vs. 0.2% (0.0, 1.3%), P<0.0001] and more exacerbations (P<0.05). Multiple regression analysis indicated that triple controller therapy significantly reduced the risk of uncontrolled asthma [OR =0.32, 95% CI =(0.14, 0.75)]. CONCLUSIONS: Although there is a relatively low proportion of severe refractory asthma based on ERS/ATS criteria, two of five patients with asthma in China are uncontrolled, displaying more psychological symptoms and reduced work productivity. Substantial gain in asthma control is obtained by triple controller therapy and this may be a promising therapeutic option for persistent asthma.